Health and social care providers' perspectives of older people's drinking: a systematic review and thematic synthesis of qualitative studies. (21st February 2020) - Bareham, Bethany Kate; Kaner, Eileen; Spencer, Liam; Hanratty, Barbara
Abstract: Background: alcohol may increase risks to late-life health, due to its impact on conditions or medication. Older adults must weigh up the potential risks of drinking against perceived benefits associated with positive roles of alcohol in their social lives. Health and social care workers are in a key position to support older people's decisions about their alcohol use. Objective: to systematically review and synthesise qualitative studies exploring health and social care providers' views and experiences of older people's drinking and its management in care services. Method: a pre-specified search strategy was applied to five electronic databases from inception to June 2018. Grey literature, relevant journals, references and citations of included articles were searched. Two independent reviewers sifted and quality-appraised articles. Included study findings were analysed through thematic synthesis. Results: 18 unique studies were included. Four themes explained findings: uncertainty about drinking as a legitimate concern in care provision for older people; the impact of preconceptions on work with older adults; sensitivity surrounding alcohol use in later life; and negotiating responsibility for older adults' alcohol use. Discipline- and country-specific patterns are highlighted. Conclusions: reservations about addressing alcohol could mean that service providers do not intervene with older adults. Judgements of whether older care recipients' drinking warrants intervention are complex. Providers will need support and training to recognise and provide appropriate intervention for drinking amongst older care recipients.